Effect Of Genotype, Age And Season On Hatchability Of Egg (Bangladesh Journal of Animal Science, 2012)
The study was conducted to study the effects of genotype and age of hen and hatching season on hatchability of egg. Hatching eggs were collected from hens having three genotypes viz. White Leghorn (WLH), Rhode Island Red (RIR) and Fayoumi covering three age groups (28 to 40, 41 to 60 and 61 weeks & above) at winter, monsoon and summer seasons. The study revealed that the highest (P